BRUCE ARONSON / JOONGI KIM (eds.): Corporate Governance in Asia. A Comparative Approach - Bälz, Moritz (Zeitschrift für Japanisches Recht, 2019)
Cambridge University Press, Cambridge / New York 2019, XVII, 418 pp., £ 89.99 (Hardback), £ 34.99 (Paperback), $ 40.00 (eBook) ISBN 978-1-108-42077-8 (Hardback), 978-1-108-43087-6 (Paperback), 978-1-108-35974-0 (eBook)